Calibration of the ångström-Prescott Equation for Solar Radiation Estimation in Minas Gerais - Lucas Santos do Patrocínio Figueiró; Lucas Fernandes Meira; Lucas da Costa Santos (Revista Brasileira de Meteorologia)
Abstract Solar energy emerges as a promising sustainable source of energy, capable of meeting energy demand and mitigating issues related to climate change. To evaluate its availability, we can use empirical models such as the Angstrom-Prescott (AP) equation. In this context, our objective was to calibrate and assess the AP model to estimate global solar radiation (Rs) in Minas Gerais. We utilized solar radiation and insolation data from seven municipalities in the state, extracted from the National Institute of Meteorology (INMET), calibrating the model's coefficients through linear regression. After calculating Rs with the calibrated linear and angular coefficient values, we evaluated the accuracy of the estimative by comparing it with observed data. For this, we used the following statistical indicators: linear, angular, determination, and correlation coefficients; mean absolute error; root mean square error; concordance index; and performance index. The results indicated that the model can be an effective tool for estimating Rs in the region (performance index above 0.80, except in one municipality). The use of the calibrated coefficients presented in this work or the standard method are both effective and show no difference between them. The Angstrom-Prescott model proved to be effective in estimating solar radiation in Minas Gerais, with results highlighting its accuracy and applicability.